EDUKASI SEKSUAL UNTUK SISWA SEKOLAH DASAR DI PESISIR KABUPATEN LAMONGAN MELALUI MEDIA BONEKA DAN LAGU - Holy Ichda Wahyuni; Wellia Dwi Anugraini; Ayu Denada Tri Laraswati (Jurnal Abadimas Adi Buana, 2023)
Indonesia is considered to have entered an emergency for sexual violence against children. Every year, cases of sexual violence summarized from various sources show an increasing number. Many factors later become triggers, one of which is the lack of provision of sexual education, especially for early childhood/elementary schools. Based on this background, sexual education activities for elementary school students are important to do. The purpose of this activity is to provide an understanding to children about the dangers of sexual violence, about body authority, which body parts should not be touched by other people, and what should be done if children receive unpleasant treatment, contain elements of coercion and lead to sexual harassment. This activity was carried out at MI Muhammadiya 1 and 2 Paciran, Lamongan District, with the target community being fifth and sixth grade elementary school students, along with their teachers. This activity was carried out on August 22, 2022. The method used is a method of providing direct education through a fun learning approach using puppets and songs as media.